2021
DOI: 10.1002/spe.2969
|View full text |Cite
|
Sign up to set email alerts
|

An approach to forecast impact of Covid‐19 using supervised machine learning model

Abstract: The Covid-19 pandemic has emerged as one of the most disquieting worldwide public health emergencies of the 21st century and has thrown into sharp relief, among other factors, the dire need for robust forecasting techniques for disease detection, alleviation as well as prevention. Forecasting has been one of the most powerful statistical methods employed the world over in various disciplines for detecting and analyzing trends and predicting future outcomes based on which timely and mitigating actions can be un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 45 publications
(47 reference statements)
0
37
0
Order By: Relevance
“…17 The estimates from our ML model for Fiji (2011) and Samoa (2013) suggested that the mean salt consumption was 8.9 g/day and 9.6 g/day, respectively. A survey in Vanuatu in 2016 based on 24-hour urine sample informed that the mean salt intake was 5.9 g/day; 18 our estimate for the year 2011was 8.6 g/day. In 2009 in Vietnam a survey with SU samples revealed that the mean salt consumption was 9.9 g/day; 19 our prediction for the year 2015 was 7.9.…”
Section: Research In Contextmentioning
confidence: 64%
See 3 more Smart Citations
“…17 The estimates from our ML model for Fiji (2011) and Samoa (2013) suggested that the mean salt consumption was 8.9 g/day and 9.6 g/day, respectively. A survey in Vanuatu in 2016 based on 24-hour urine sample informed that the mean salt intake was 5.9 g/day; 18 our estimate for the year 2011was 8.6 g/day. In 2009 in Vietnam a survey with SU samples revealed that the mean salt consumption was 9.9 g/day; 19 our prediction for the year 2015 was 7.9.…”
Section: Research In Contextmentioning
confidence: 64%
“…ML models have been used extensively to predict relevant clinical outcomes (e.g., mortality) and epidemiological indicators (e.g., forecasting COVID-19 cases). [20][21][22][23][24] Furthermore, ML algorithms have proven to be useful for understanding complex outcomes (e.g., identifying clusters of people with diabetes) based on simple predictors (e.g., BMI) in nationally-representative survey data. [25][26][27] Our work complements the current evidence on ML algorithms by demonstrating its use in a relevant field: population salt consumption.…”
Section: Public Health Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the near future innovative information integration system software design could be the solution to achieve sustainability during pandemic like situations. 75 , 76 , 77 , 78 , 79 …”
Section: Key Findingsmentioning
confidence: 99%